Artificial Fibers—The Implications of the Digital for Archival Access - Moss, Michael; Thomas, David; Gollins, Timothy (Frontiers in Digital Humanities, 2018)
This article explores how current methods and approaches in archives are under serious challenge because of the changes brought about to the move to the digital. The availability of digital records has meant that new needs and new possibilities have opened up for users, including new ways of reading. The nature of archives themselves are changing – they are moving from being collections of individual texts to be pored over to data to be made sense of. New tools and techniques have emerged and are available right here now which offer radical new possibilities for research, but these bring new challenges about trust and the sheer volume of records to be handled. The traditional approaches of applying metadata to facilitate the finding of relevant material and of regarding digital documents as something like electronic paper is no long viable. What is needed is a new approach in which archivists and scholarly researchers see archives as collections of data which are capable of analysis by a range of sophisticated tools and which are capable of being interpreted in a range of different ways.